Towards holistic grammar engineering and testing : grafting treebank maintenance into the grammar revision cycle - Bond, Francis (2011)
We present a new methodology for the semiautomated maintenance of a treebank built from analyses of a computational grammar and gauge the effort required for each update cycle. Based on a decade of large-scale grammar engineering experience, we propose a tight integration of treebank maintenance with the continuous evolution of a ‘deep’ computational grammar.